Quasi-BICs enhanced second harmonic generation from WSe2 monolayer - Ren Peiwen; Huang Zhuo; Luo Song; Liu Jia; Dong Xiaoxiang; Zhang Hua; Li Jianfeng; Yang Zhilin (Nanophotonics)
Quasi-bound states in the continuum (quasi-BICs) offer unique advantages in enhancing nonlinear optical processes and advancing the development of active optical devices. Here, the tunable robust quasi-BICs resonances are experimentally achieved through the engineering of multiple-hole Si-metasurface. Notably, the quasi-BICs mode exhibits flat bands with minimal dispersion at a wide range of incident angles, as demonstrated by the angle-resolved spectroscopy measurements. Furthermore, we demonstrate a giant second-harmonic generation (SHG) enhancement by coupling a WSe2 monolayer to the quasi-BICs hosted in the metasurface. Leveraging the strong local electric field and high state density of the observed quasi-BICs, the SHG from the WSe2 monolayer can be enhanced by more than two orders of magnitude. Our work paves the way for effectively enhancing nonlinear optical processes in two dimensional (2D) materials within the framework of silicon photonics and is expected to be applied in nonlinear optical devices.